Ionically and Enzymatically Dual Cross-Linked Oxidized Alginate Gelatin Hydrogels with Tunable Stiffness and Degradation Behavior for Tissue Engineering - Distler, Thomas; Mcdonald, Kilian; Heid, Susanne; Karakaya, Emine; Detsch, Rainer; Boccaccini, Aldo R. (ACS Biomaterials Science and Engineering, 2020)
Hydrogels that allow for the successful long-term in vitro culture of cell-biomaterial systems to enable the maturation of tissue engineering constructs are highly relevant in regenerative medicine. Naturally derived polysaccharide-based hydrogels promise to be one material group with enough versatility and chemical functionalization capability to tackle the challenges associated with long-term cell culture. We report a marine derived oxidized alginate, alginate dialdehyde (ADA), and gelatin (GEL) system (ADA-GEL), which is cross-linked via ionic (Ca2+) and enzymatic (microbial transglutaminase, mTG) interaction to form dually cross-linked hydrogels. The cross-linking approach allowed us to tailor the stiffness of the hydrogels in a wide range (from <5 to 120 kPa), without altering the initial ADA and GEL hydrogel chemistry. It was possible to control the degradation behavior of the hydrogels to be stable for up to 30 days of incubation. Increasing concentrations of mTG cross-linker solutions allowed us to tune the degradation behavior of the ADA-GEL hydrogels from fast (<7 days) to moderate (14 days) and slow (>30 days) degradation kinetics. The cytocompatibility of mTG cross-linked ADA-GEL was assessed using NIH-3T3 fibroblasts and ATDC-5 mouse teratocarcinoma cells. Both cell types showed highly increased cellular attachment on mTG cross-linked ADA-GEL in comparison to Ca2+ cross-linked hydrogels. In addition, ATDC-5 cells showed a higher proliferation on mTG cross-linked ADA-GEL hydrogels in comparison to tissue culture polystyrene control substrates. Further, the attachment of human umbilical vein endothelial cells (HUVEC) on ADA-GEL (+) mTG was confirmed, proving the suitability of mTG+Ca2+ cross-linked ADA-GEL for several cell types. Summarizing, a promising platform to control the properties of ADA-GEL hydrogels is presented, with the potential to be applied in long-term cell culture investigations such as cartilage, bone, and blood-vessel engineering, as well as for biofabrication.
CRIS-Team WoS Importer:2020-08-07